Chemical Composition of Different Parts of the Vitex agnus-castus L. Essential Oils and Their In-Vitro Cytotoxic Activities - İNAL, EBRAR; İnal E.; ULUSOY, ŞEYMA; Nath E. Ö.; KARTAL, MURAT; Abudayyak M.; Ulusoy Ş.; İnan H. A.; Cicek M.; Kartal M. (My University, 2023)
The essential oil (EO) compositions and chemotypes of the important ethnomedicinal plantVitex agnus-castusL. flowers, leaves, and fruits collected from Türkiye (Balıkesir and İstanbul) were identified in the present study. Different parts of theV. agnus-castusEO’sin-vitrocytotoxic effects on the MCF-7 (human breast adenocarcinoma) and A549 (human lung carcinoma) human-origin cell lines were anaylzed in the current study. The composition of hydrodistiled EOs extracted from flowers, leaves, and fruits ofV. agnus-castuswere analyzed by GC–FID/MS. Monoterpene hydrocarbons and oxygenated monoterpene compounds were detected as the predominant component class of theV. agnus-castus. EOs extracted from Balıkesir region were defined as the \"α-pinene-1,8-cineole\" chemotype, while EOs extracted from İstanbul region were defined as the \"sabinene-1,8-cineole\" chemotype. Sesquiterpene hydrocarbons constituted more than 20% of the compounds in the EOs extracted from the flowers. To the best of our knowledge, this study is the first to analyze thein-vitrocytotoxic effects of flowers. This study is also the first to show thein-vitrocytotoxic effects of fruit, the most commonly used part of the plant, EO on the MCF-7 cell line. Balıkesir region’s EOs were observed as more potent -especially the purple flower’s IC50 is about 4.68 µg/mL on the MCF7 cell line- than İstanbul regions, which might be attributed to the higher amount ofα-pinene, caryophyllene, and limonene content. Our results indicated that theV. agnus-castusEOs, which containα-pinene, 1,8-cineole, caryophyllene, and limonene as major components, showed relatively high cytotoxic effects compared to the control groups on the MCF7 and A549 cell lines.
Keywords: Eczacılık; Sağlık Bilimleri; Pharmacology and Therapeutics; Health Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; Clinical Medicine (MED); Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Yaşam Bilimleri; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Life Sciences